Analisis Pelayanan Obstetri Neonatal Emergensi Dasar Berdasarkan Program QA di Puskesmas PONED X Kabupaten Bondowoso - Asti Nuris; Al- Munawir; Dewi Rokhmah (Multidisciplinary Journal, 2020)
As health service provider, primary health care should provide qualified and satisfied service among patients. The PONED is government’s program to reduce the maternal mortality rate. On the other hand, QA is a program used to preserve the quality of primary health care. The aim of this study is to analyze basic emergency neonatal obstetric by using QA program. This is qualitative study, where there were four informants in this study, consist of key-, main-, and additional- informant. Furthermore, the data was collected by in-depth interview. This study found that the variable of input of QA has not fulfilled and supported the implementation of PONED. The variable of process has not performed in accordance with the procedure yet. On the other hand, the variable of output showed that the performance has not been optimal yet. Keyword: PONED, QA, Quality